A Direct Role for the CD1b Endogenous Spacer in the Recognition of a Mycobacterium tuberculosis Antigen by T-Cell Receptors - Camacho, Frank; Moreno, Ernesto; Garcia-Alles, Luis F.; Chinea Santiago, Glay; Gilleron, Martine; Vasquez, Aleikar; Choong, Yee Siew; Reyes, Fátima; Norazmi, Mohd Nor; Sarmiento, Maria E.; Acosta, Armando (Frontiers in Immunology, 2020)
Lipids, glycolipids and lipopeptides derived from Mycobacterium tuberculosis (Mtb) are presented to T cells by monomorphic molecules known as CD1. This is the case of the Mtb-specific sulfoglycolipid Ac2SGL, which is presented by CD1b molecules and is recognized by T cells found in tuberculosis (TB) patients and in individuals with latent infections. Our group, using filamentous phage display technology, obtained two specific ligands against the CD1b-Ac2SGL complex: (i) a single chain T cell receptor (scTCR) from a human T cell clone recognizing the CD1b-AcSGL complex; and (ii) a light chain domain antibody (dAbκ11). Both ligands showed lower reactivity to a synthetic analog of Ac2SGL (SGL12), having a shorter acyl chain as compared to the natural antigen. Here we put forward the hypothesis that the CD1b endogenous spacer lipid (EnSpacer) plays an important role in the recognition of the CD1b-Ac2SGL complex by specific T cells. To support this hypothesis we combined: (a) molecular binding assays for both the scTCR and the dAbκ11 antibody domain against a small panel of synthetic Ac2SGL analogs having different acyl chains, (b) molecular modeling of the CD1b-Ac2SGL/EnSpacer complex, and (c) modeling of the interactions of this complex with the scTCR. Our results contribute to understand the mechanisms of lipid presentation by CD1b molecules and their interactions with T-cell receptors and other specific ligands, which may help to develop specific tools targeting Mtb infected cells for therapeutic and diagnostic applications.